Limited Access to Health Services and Pregnancy Risks - Irmadani, Andi Syarifah; Rikhaniarti, Tri; Ibrahim, Sitti Hasrah; Irwan, Hadriani (Advances in Healthcare Research, 2025)
Purpose: This study aims to examine the limitations of access to health services and their relationship to increased pregnancy risk in Indonesia, highlighting the interacting geographical, socioeconomic, cultural, and policy factors that shape maternal access disparities. Research Method: This study employs a qualitative approach, utilizing the Systematic Literature Review (SLR) method to analyze academic literature published between 2015 and 2025. The search was conducted comprehensively through searches in reputable international journals from publishers Elsevier, Emerald, Wiley, and Springer. Results and Discussion: The study's results indicate that structural factors, including low socioeconomic status, geographical isolation, and a shortage of trained healthcare workers, primarily cause limited access to maternal health services. In addition, socio-cultural factors such as the dominance of non-medical personnel and gender norms also contribute to delays in accessing medical services. The mismatch between national policies and local needs exacerbates service gaps and increases the risk of pregnancy complications. Implications: This study highlights the importance of a multidisciplinary and contextual approach in developing maternal health policies. Community-based strategies that take into account the socio-cultural context and strengthen primary services and health literacy are needed as long-term, sustainable interventions.